Excessive sweating: an uncommon sign of basilar artery occlusion. Issue 3 (March 1991) - Awada, A; Ammar, A; al-Rajeh, S; Borollosi, M
Abstract : Excessive sweating of the face and, to a lesser degree, of the thorax and limbs, occurred after basilar artery occlusion in a 15 year old Saudi boy. Magnetic resonance imaging (MRI) showed a limited bilateral paramedian infarction of the rostral ventral pons. Basilar artery occlusion in children and adolescents is a rarity. Excessive sweating following such a stroke is rare in any age group. Clinico-anatomical correlations are discussed.